Prayer and Worship a spiritual formation guide - Lynda L. Graybeal; Julia L. Roller; Roller, Julia L. (New York HarperCollins e-books, 2009)
Discusses how to utilize the Psalms and prayer to come before God and enter His presence.
Keywords: Worship - Christianity; Prayer -- Christianity. Worship programs. Spiritual formation. Spiritual life -- Christianity. RELIGION -- Christian Life -- Prayer